Bis(tri‐tert‐butylphosphine)palladium(0)‐Catalyzed Iodine–Fluorine Exchange at closo‐Carboranes. Issue 24 (19th June 2018) - Ishita, Keisuke; Khalil, Ahmed; Tiwari, Rohit; Gallucci, Judith; Tjarks, Werner
Abstract : The bis(tri‐ tert ‐butylphosphine)palladium(0) [Pd( t Bu3 P)2 ]‐catalyzed synthesis of fluorinated closo ‐carboranes from 3D aromatic iodo‐ closo ‐carboranes by nucleophilic halogen exchange using silver(I) fluoride is described. Fluorination of 2‐iodo‐ closo ‐ p ‐carborane proceeded more readily than that of 9‐iodo‐ closo ‐ m ‐carborane. Iodine–fluorine exchange at 9‐iodo‐ closo ‐ o ‐carborane was not successful yielding instead a charge‐compensated dibutylphosphonio nido ‐ o ‐carborane. The described methodology advances the understanding of nucleophilic fluorination at aromatic systems by Pd 0 /Pd II catalysis. With further optimization, it could find application in the synthesis of 18 F‐labeled carboranyl diagnostics for biomedical applications. Abstract : The bis(tri‐ tert ‐butylphosphine)palladium(0) [Pd( t Bu3 P)2 ]‐catalyzed synthesis of fluorinated closo ‐carboranes from 3D aromatic iodo‐ closo ‐carboranes by nucleophilic halogen exchange using silver(I) fluoride is described. The described methodology advances the understanding of nucleophilic fluorination at aromatic systems by Pd 0 /Pd II catalysis.